What predicts the alleviation of Covid-related future anxiety in schoolchildren 6 to 9 months into the pandemic? - Voltmer, Katharina; von Salisch, Maria (Frontiers in Psychology, 2023)
Although the first Covid-19-related lockdown in the Spring of 2020 has contributed to an increase in mental health problems in many children worldwide, less is known about the longer-term effects of the pandemic on their (future) anxiety. In order to examine resilience factors against children's Covid-related future anxiety (CRFA), N = 140 children (48,6% female) in 3 rd and 4 th grade classrooms in Northern Germany were asked to self-report about their CRFA, their anxiety, and the social climate in their classrooms in September (T1) and December 2020 (T2). Results indicate that 18.6% of the children experienced CRFA "often" in at least one item of the CRFA scale at T1. CRFA was more pronounced in girls and in children from immigrant families. Changes in children's CRFA between T1 and T2 were predicted by changes in their anxiety and changes in classroom climate. Children in classrooms with increasing levels of peer support tended to have decreasing levels of CRFA, whereas their agemates' CRFA in less supportive classrooms tended to increase over time.These results suggest that peer and teacher social support may bolster children's resilience against future anxiety in challenging times. Implications for teachers and schools are discussed.